The therapeutic potential of curcumin: A review of clinical trials - Salehi, Bahare; Stojanović-Radić, Zorica; Matejić, Jelena; Sharifi-Rad, Mehdi; Anil Kumar, Nanjangud V.; Martins, Natália; Sharifi-Rad, Javad (European journal of medicinal chemistry, 2019)
Curcuma longa L., its derived extracts and even its major compound curcumin has a long history of use and doubtless effectiveness, reported through increasingly detailed in vitro, ex vivo, in vivo and even clinical trials. Regarding its biological effects, multiple health-promoting, disease-preventing and even treatment attributes has been remarkably highlighted. Clinical trials, although have increased in a progressive manner, significant disproportionalities have been stated in terms of biological effects assessment. In this sense, the present report aims to provide an extensive overview to curcumin therapeutic effects in human subjects. For that, clinical trials assessing the curcumin effect on inflammation, skin, eye, central nervous system, respiratory, cardiovascular, gastrointestinal, urogenital and metabolic disorders are here presented and discussed. A special emphasis was also given to curcumin activity on intoxications and multiple malignant diseases. [Display omitted] •Curcuma longa L., and its main bioactive constituent, curcumin, have a wide spectrum of biological potentialities.•Promising in vitro and in vivo therapeutic effects have been markedly reported.•Curcumin therapeutic effects in human subjects are carefully discussed here.•Curcumin anti-inflammatory and cardioprotective effects are the most often investigated.•Renowned benefits on malignant diseases, gastrointestinal and central nervous system have also been demonstrated.